Evaluation of Quality of Life for Women With Breast Cancer - Khalifa, Mohammed F; Al Ghuraibawi, Zahraa Adnan Ghadhban; Hade, Istikrar M; Ali Mahdi, Montadher (Scripta Medica, 2024)
Background/Aim: One of the therapeutic outcome metrics for women with breast cancer is quality of life (QoL). The purpose of the following study was to evaluate the QoL of women with breast cancer who were getting therapy or on follow-up at the Oncology Teaching Hospital in Medical City, Baghdad, Iraq.Methods: A convenient sample of 100 women was selected from the Teaching Oncology Hospital at Medical City in Baghdad City. For the purposes of the study, a questionnaire was constructed. Physical, role, emotional, cognitive and social functioning were its five functional domains. Each study participant received a questionnaire explaining how to complete it, along with a form requesting their approval to remain anonymous. They also got the opportunity to leave the study at any time without being provided an explanation. A panel of 10 experts determined the questionnaire's content validity and its internal consistency reliability was calculated using the split-half method and the Cronbach α correlation coefficient of r = 0.92. Data were collected using the study questionnaire and analysed using a descriptive statistical data analysis approach based on frequency and percent.Results: The study findings depict that most of the women with breast cancer were 31-49 year old and they accounted for 43 % of the studied sample. Most of these women had problems with their emotional, social and role functioning.Conclusion: Breast cancer affects many elements of life, but it has the largest influence in modern culture on social and emotional functioning, as well as role functioning. A multidisciplinary team working with affected women would be advantageous in enhancing the QoL of breast cancer patients, particularly in the most compromised aspects of their health.